2010
DOI: 10.1345/aph.1p030
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin-Induced Hemolytic Anemia in a Child with Glucose 6-Phosphate Isomerase Deficiency

Abstract: This report reinforces the hypothesis that a drug-sensitivity reaction is closely related to a genetically transmitted enzyme deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
(5 reference statements)
2
10
0
Order By: Relevance
“…The only reported case of amoxicillin-associate hemolytic anemia occurred a patient with G6PD isomerase deficiency receiving 50mg/kg/ day, and no cases have been reported in patients with G6PDD. [1] Although generally safe for patients with G6PDD, acetaminophen has numerous potential mechanisms that may predispose susceptible individuals to oxidative stressors. It is well established that acetaminophen, through its toxic metabolite N-acetyl-p-benzoquinoneimine (NAPQI), causes oxidative hepatocellular damage after depletion of glutathione (GSH).…”
mentioning
confidence: 99%
“…The only reported case of amoxicillin-associate hemolytic anemia occurred a patient with G6PD isomerase deficiency receiving 50mg/kg/ day, and no cases have been reported in patients with G6PDD. [1] Although generally safe for patients with G6PDD, acetaminophen has numerous potential mechanisms that may predispose susceptible individuals to oxidative stressors. It is well established that acetaminophen, through its toxic metabolite N-acetyl-p-benzoquinoneimine (NAPQI), causes oxidative hepatocellular damage after depletion of glutathione (GSH).…”
mentioning
confidence: 99%
“…Lack of NADPH can be a cause of destabilization of the erythrocyte membrane, lysis, and the onset of chronic hemolytic anemia. Lack of reducing agents such as NADPH and GSH in the presence of GPI deficiency may be the cause of a hemolytic crisis due to exogenous oxidants such as infections or drugs (Rossi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…- Rossi et al (2010) reported on nonimmune hemolytic anemia caused by amoxicillin in a child with a GPI deficiency. Decreasing the content of reducing equivalents in case of deficiency of this enzyme can lead to impairment of the system that removes free radicals generated by antibiotics, thereby resulting in perioxidative damage to hemoglobin, red blood cell enzymes, and soluble constituents, thereby leading to hemolytic crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this condition, the erythrocyte membrane loses its stabilization and a chronic non-spherocytic anemia develops. In case of exposure to oxidants including viral infections or antibiotherapy, acute hemolytic attacks may be observed as a result of decreased synthesis of antioxidant substances (5). Hydrops fetalis may even be observed, when the disease has a severe course (6).…”
Section: Discussionmentioning
confidence: 99%